Simulation behaviour of fire response to fire resistance steel beams - Wong, Michael Sie Ung (2012)
High temperature is one of the factor that caused the structure to be severe and would undermine the soundness of the building. Therefore, it is very important to introduce fire safety measures appropriate to the building designer design a building before. Recent introduction of computer-based code has been helping and improving the fire resistance rating on the model. To evaluate fire resistance to the structure of steel, this is expected to alter the properties of steel used as input data. To ensure safety of the steel structure after exposure to fire, it is important to understand the effects and response to high temperature. At high temperatures, stainless steel and shape retention were stronger than conventional steel structures. In addition, the relationship between strength and stiffness at high temperatures influenced by buckling of retaliation against the structural components. Several sets of numerical experiment using the computer software LUSAS was conducted to investigate the effect of reaction to fire steel beams and columns based on a real fire as well as the burdens. Finite element model is valid based on experimental data, and the effect of high temperature on steel beams and columns can be described. A valid model is used to carry out some parametric research. This research emphasizes to find the strength of stainless steel in high temperature, 25°C, 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C and 800°C. The test results show the method to fire appropriate to extend the fire exposure time, reducing the change of structure, and increase the critical temperature of the column to beam type connection.